2016
DOI: 10.1111/jar.12303
|View full text |Cite
|
Sign up to set email alerts
|

Parents with Intellectual Disabilities Experiencing Challenging Child Routines: A Pilot Study Using Embedded Self‐Determination Practices

Abstract: Implications for future research and replication of this pilot study are discussed.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0
1

Year Published

2017
2017
2021
2021

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(6 citation statements)
references
References 46 publications
0
5
0
1
Order By: Relevance
“…Another trend in the intervention literature is to adapt existing parent training programs for parents with IDD. Recent studies have shown promising but variable results, for adaptations of Triple P-positive parenting program [51], parent-child interaction therapy [52], and positive behavior support [49]. An RCT of an adaptation of video-feedback intervention to promote positive parenting and sensitive discipline did not significantly improve ratings of targeted parenting skills [53].…”
Section: Recent Trends In Interventions For Parents With Idd and Theimentioning
confidence: 99%
“…Another trend in the intervention literature is to adapt existing parent training programs for parents with IDD. Recent studies have shown promising but variable results, for adaptations of Triple P-positive parenting program [51], parent-child interaction therapy [52], and positive behavior support [49]. An RCT of an adaptation of video-feedback intervention to promote positive parenting and sensitive discipline did not significantly improve ratings of targeted parenting skills [53].…”
Section: Recent Trends In Interventions For Parents With Idd and Theimentioning
confidence: 99%
“…Reviewing the evidence, Wade, Llewellyn, and Matthews (, p. 362) concluded that “home‐based behavioural parent training leads to successful learning of parenting skills among parents with intellectual disability”. In this special issue, Hodes, Meppelder, de Moor, Kef, and Shuengel (the Netherlands), and Knowles, Blakely, Hansen, and Machalicek (the USA) augment the evidence base, further demonstrating the potential benefit of training that is matched to the parent's learning needs and priorities. Hodes and colleagues conducted one of the largest randomized controlled trials in the field to date and found that a video‐feedback intervention targeting parental sensitivity/responsiveness was effective in reducing child‐related parenting stress.…”
Section: Parenting Skills and Trainingmentioning
confidence: 91%
“…Hodes and colleagues conducted one of the largest randomized controlled trials in the field to date and found that a video‐feedback intervention targeting parental sensitivity/responsiveness was effective in reducing child‐related parenting stress. Novel components in each of the parenting interventions, including the embedding of self‐determination practices (Knowles et al.), and use of video feedback (Hodes et al.) will be of interest to even the most experienced parent educators and family support practitioners. As the evidence base of training methods for parents with intellectual disabilities continues to grow, there is little excuse for child welfare and other services to say “nothing can be done but to take away the child.”…”
Section: Parenting Skills and Trainingmentioning
confidence: 99%
“…A third characteristic of research-informed parenting skills training is responsiveness to parental priorities and choices: Parents with ID are known to learn best when there is respect and trust between parents and support providers, when they can choose what they want to learn, are motivated, and are offered support in a way and at a pace that is right for them (Booth & Booth, 2003). Knowles et al (2017) found that explicitly embedding selfdetermination practices into parenting skill trainingincluding collaborative goal setting, joint action planning, and parental self-monitoring-may foster engagement and enhance learning. A fourth characteristic is in situ learning; effective training is usually delivered in the family home or another environment wherein new skills will be applied (Feldman & Tahir, 2016).…”
Section: Parenting Skills Trainingmentioning
confidence: 99%